Gouda Moroccan Dutch: Linguistic Ideology and Practice in an Urban Youth Variety - Mourigh, Khalid (AAeO - Afrikanistik-Aegyptologie-Online, 2023)
This study describes certain aspects of the Moroccan Dutch youth variety in Gouda (the Netherlands). It adopts a critical approach with regard to youth language using current sociolinguistic concepts and tools. This study contains two parts. The first part is largely focused on methods and metalinguistic analysis, the second part is the description of the linguistic data which is subdivided in a phonetic part and a morphosyntactic part.This a fieldwork-based study which includes material based on a number of interviews with Moroccan Dutch teenagers. While the amount of fieldwork was sufficient for the initial goal of the study, namely a description of the phonetics, for it to dig deeper and uncover linguistic usage and ideology, metalinguistic data was collected as well. These data were used to uncover information, not only about language practice, but also about tribal origins, cultural stereotypes and heritage language use. Interethnic language practices, accent and code switching are included as well.The second part deals with the salient segmental phonetics, beginning with the consonants and ending with the vowels. Possible substrate influence, mainly based on Tarifiyt Berber, and intergenerational and interethnic differences are sketched as well. In the final part some conspicuous morphosyntactic phenomena are touched upon, such as grammatical gender and the genitive.To conclude, this study aims to provide an insight from a sociolinguistic perspective into Gouda Moroccan Dutch language practice, form and ideology. That is, it describes social interaction and linguistic practice from a multifocal and dynamic viewpoint.